Periodic and long-term changeability of salinity of South Atlantic is from data of measurings at the Antarctic Akademic Vernadsky Station - Belokrinitskaya, L. M.; Klok, S. V.; Kruchenitskiy, G. M.; Skorobagaty, T. V. (Ukrainian Antarctic Journal, 2008)
The methods of linear and nonlinear regressive analysis are get the parameters of periodic changeability and trendov of salinity, and also temperatures of water and air from data of supervisions for 2000-2006. It is set that except for seasonal vibrations the transferred parameters are subject to more slow oscillation with the basic period of 3. Salinity and temperature of water have meaningful negative trendy statistically. It is shown that these trendy is formed due to the synchronous negative troop landings which are conditioned growth of influx lead fresh ot destruction of ice shield of Antarctic Region during the Antarctic summer.